The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/rs12061025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring of a Mid-Rise Building by Real-Aperture Radar Interferometer: Advantages and Limitations

Abstract: In this paper, remote and in situ techniques to estimate the dynamic response of a building to ambient vibration are reported: data acquired through a real-aperture radar (RAR) interferometer and conventional accelerometers are analyzed. A five-story reinforced concrete housing building, which was damaged during the May 11th 2011 Lorca (Spain) earthquake, is used as a case study. The building was monitored using both types of instruments. The dynamic properties of the building are estimated first taking accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…GBRAR systems can be suitable for continuously monitoring fast structural displacements, such as mechanical vibration, with a data acquisition rate of a fraction of a second (Rodrigues and Li, 2021). To this end, various case studies, such as bridges (Huang et al, 2020) and buildings (Alva et al, 2020), have been investigated to evaluate GBRAR capabilities for SHM. A study on the feasibility of vibration monitoring of tall structures by combining a laser scanner and GBRAR was presented by Artese and Nico (2020).…”
Section: Introductionmentioning
confidence: 99%
“…GBRAR systems can be suitable for continuously monitoring fast structural displacements, such as mechanical vibration, with a data acquisition rate of a fraction of a second (Rodrigues and Li, 2021). To this end, various case studies, such as bridges (Huang et al, 2020) and buildings (Alva et al, 2020), have been investigated to evaluate GBRAR capabilities for SHM. A study on the feasibility of vibration monitoring of tall structures by combining a laser scanner and GBRAR was presented by Artese and Nico (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study of acceleration or vibration is another relevant method to compute the dynamic performance of structures [ 6 , 18 , 19 ]. However, most of the research on vibration extraction is developed with the help of acceleration devices or vibrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Nico et al 12 measured the displacements of telecommunications towers by a ground‐based radar interferometry and identified the structural frequencies. Alva et al used a real‐aperture radar to perform displacement‐based dynamic monitoring under environmental excitations to estimate the fundamental frequency of a damaged mid‐rise building 13 . Sofi et al 14 employed an interferometric radar system to determine dynamic characteristics of high‐rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Alva et al used a real-aperture radar to perform displacement-based dynamic monitoring under environmental excitations to estimate the fundamental frequency of a damaged mid-rise building. 13 Sofi et al 14 employed an interferometric radar system to determine dynamic characteristics of high-rise buildings. However, it was reported that the interferometric radar system was sensitive to ambient noise and it is difficult to identify the modal parameters in high orders.…”
Section: Introductionmentioning
confidence: 99%